The use of Cannabis sativa in treatment of Alzheimer - Freitas, Alessandra Karolyne Lopes (2022)
Alzheimer's disease is becoming increasingly common among the elderly, a degenerative, progressive and irreversible neurological disease. The treatment is carried out through drugs with the objective of minimizing the disturbances of the disease and, among the existing pharmacological treatments, those with drugs based on Cannabis sativa stand out. The study aimed to analyze in the scientific literature the therapeutic use of Cannabis sativa in the treatment of Alzheimer's disease. An integrative literature review was carried out, with a qualitative approach, with analyzes carried out online in national journals indexed in the electronic libraries of the following databases: Scientific Electronic Library Online (SciELO); Medical Literature Analysis and Retrieval System Online (Medline); System of Latin American and Caribbean Literature on Health Sciences (LILACS) and Virtual Health Library (VHL). With the data, a record was generated. Among the selected works, only ten presented studies according to the proposed theme. It was observed that the use of Cannabis sativa is effective for the pharmacological treatment of Alzheimer's disease, whose research points to important advantages in its use. It is concluded that research on the advantages of using cannabidiol for therapeutic purposes is essential for the advancement of medicine and for breaking paradigms about Cannabis.